Efektivitas Formasi Tempat Duduk Siswa Kelas VII terhadap Hasil Belajar - Atini Ilannur; Arwin Achmad; Rini Rita T. Marpaung (Universitas Lampung, 2017)
This study aimed to determine the effectiveness of seating formation towards students learning outcomes on interaction between organisms and their environment subject in junior high school 4 Pringsewu. The research design was pretest-posttest non-equivalent groups. The population were all VII grades students and samples were VII1, VII2, and VII3 grades student which were selected by purposive sampling. This research data were the result of students learning obtained through pretest-posttest, students self assessment affective aspects and students psychomotor aspects observation sheets. Cognitive aspects data were analyzed by One-Way Anova test and t-test. The data of affective and psychomotor aspects were analyzed using Qualitative Achievement Index and calculated score improvement. The results showed that the experimental class I had N-gain and the highest score improvement each aspect. So, there were differences in the effectiveness of the three seating formations towards students learning outcomes.Penelitian ini bertujuan untuk mengetahui efektivitas formasi tempat duduk terhadap hasil belajar siswa materi interaksi antar makhluk hidup dan lingkungannya di SMPN 4 Pringsewu. Penelitian ini menggunakan desain pretes-postes non- ekuivalen. Populasi penelitian ini seluruh siswa kelas VII dan sample terpilih siswa kelas VII1, VII2, dan VII3 yang diambil dengan teknik purposive sampling. Data penelitian berupa hasil belajar siswa yang diperoleh melalui pretes-postes, lembar penilaian diri afektif dan lembar pengamatan psikomotorik. Data aspek kognitif dianalisis dengan uji One-Way Anova dan uji t. Data aspek afektif dan psikomotorik dianalisis menggunakan Indeks Prestasi Kualitatif serta dihitung peningkatan nilainya. Hasil penelitian menunjukkan kelas eksperimen I memiliki N-gain dan peningkatan nilai tertinggi pada setiap aspek. Jadi, terdapat perbedaan efektivitas dari ketiga formasi tempat duduk terhadap hasil belajar siswa.Kata kunci: efektivitas, formasi tempat duduk, hasil belajar, interaksi antar makhluk hidup dan lingkungannya